If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xsquared + 14x + c = 0 Reorder the terms: adeqrsuX + c + 14x = 0 Solving adeqrsuX + c + 14x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1c' to each side of the equation. adeqrsuX + c + -1c + 14x = 0 + -1c Combine like terms: c + -1c = 0 adeqrsuX + 0 + 14x = 0 + -1c adeqrsuX + 14x = 0 + -1c Remove the zero: adeqrsuX + 14x = -1c Add '-14x' to each side of the equation. adeqrsuX + 14x + -14x = -1c + -14x Combine like terms: 14x + -14x = 0 adeqrsuX + 0 = -1c + -14x adeqrsuX = -1c + -14x Divide each side by 'deqrsuX'. a = -1cd-1e-1q-1r-1s-1u-1X-1 + -14d-1e-1q-1r-1s-1u-1xX-1 Simplifying a = -1cd-1e-1q-1r-1s-1u-1X-1 + -14d-1e-1q-1r-1s-1u-1xX-1
| 3x+X=7 | | 4(3x+7)=2(6x+14) | | 7xw*2w= | | -5A=-15 | | 5x+7/2=3x+5/4+2x+3 | | 14+6b+7-2b= | | 6(3x-4)=60 | | 2(y+4)=7(y-1) | | 1-X+X=11 | | 43/6/2 | | 4=2y+2x | | 3(3x+1)-4(2x-5)=5(x-1)-2(10-x) | | 5a+7b=9 | | 3x+5/4=2x+5 | | 3x^2-2y^2-4y-26=0 | | 5(x-3)=33 | | x^2/8 | | 6x=78-4x | | 6(x-2)-(x+1)=2 | | 10-2c=4c+11 | | -8-8-8v=2v+93 | | 30=2/5w | | 4p-8=8 | | 8-5x=3x+8 | | 2y/9=14 | | -2a+(7a-2)-[(-a)+3]= | | 15x=1/15 | | 6(5x+2)=18 | | 15x-4=11x-16 | | -2+9x=10x | | y-83=-79 | | 14-18y=7y |